Analisis cost volume profit (CVP) untuk perencanaan laba pada PT. Hasjrat Abadi Manado - Silangen, Novia Astrid; Saerang, David Paul Elia; Latjandu, Lady Diana (Yayasan Widyantara Nawasena Raharja, 2025)
Analysis is a tool that helps managers make business decisions regarding production volume, sales, costs, and profits within a company. This study aims to demonstrate the expected sales profit for 2023 based on the company's planning by analysing and determining the profit planning using cost volume profit at PT. Hasjrat Abadi Manado. The research findings show that the contribution margin and contribution margin ratio for 2023 are IDR 221,208,800,000, with a contribution margin ratio of 98.97%. The company's break-even point in terms of rupiah is IDR 1.090.997.603,280 and in units, it is 362 units. The Margin of Safety obtained is IDR 222.328.802.397 with a ratio of 99.51%. The company's profit target for 2023 is 45% of sales, which is IDR 100,538,910,000. This shows that the company has achieved its profit target, but it is important to maintain financial stability and continue to grow moving forward.